Agama dan Kebudayaan Masyarakat Perspektif Clifford Geertz - Ahmad Sugeng Riady (Jurnal Sosiologi Agama Indonesia (JSAI), 2021)
This article starts from the fact that religion and culture are two areas that often trigger pro and contra. On the one hand, there are many figures who clearly define the boundaries between religion and culture, while on the other hand there are also figures who continue to seek formulations of their relationship with the assumption that religion and culture provide mutual support. Clifford Geertz, an anthropologist born in San Francisco, contributed to the idea of religion and culture. This article uses the literature study method. The literature used is books that are supported by journals and previous research that are relevant to the topic the author raises. The result is that Clifford Geertz assesses human culture as a text that needs to be interpreted or thick description. This also applies when studying religious phenomena that occur in the midst of a society which is not only explained but come to the discovery of the meaning of these religious phenomena.